PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR (POC) DARI SAMPAH ORGANIK RUMAHTANGGADENGAN METODE KOMPOSTER SEDERHANA DI DESA H. WUKIRSARI KECAMATAN TUGUMULYO - Yunita Wardianti; Yuni Krisnawati (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
Wukirsari is a village located in Tugumulyo District, Musi Rawas Regency, South Sumatra, Indonesia, where most of the people work as farmers. The training on making liquid organic fertilizer was chosen in order to reduce household organic waste/waste which if not processed properly will cause environmental pollution and disturb the comfort of the community. Liquid organic fertilizer is the product chosen to be produced from this activity because liquid organic fertilizer has many advantages and benefits. Problems faced by partners such as the problem of household organic waste that pollutes the environment and disturbs the comfort of residents, this happens because the community does not understand how to process it, besides the lack of community knowledge and skills in making liquid organic fertilizer, even though liquid organic fertilizer has many benefits Therefore, it is necessary to conduct training activities on the manufacture of liquid organic fertilizer based on household organic waste. The method used is starting from preparation, socialization, and training. So it is expected that the output will be in the form of increasing knowledge and skills of the community in making liquid organic fertilizer, and creating products. The result of this activity is the implementation of socialization activities so that there is an increase in partner knowledge with an N-Gain value of 0.8 in the high category. In addition, the implementation of training activities on the manufacture of liquid organic fertilizers that provide partners' skills in making liquid organic fertilizers with a value of 92.9 in the very good category and the creation of products in the form of ready-to-use liquid organic fertilizers